Impact of oil revenue on economic growth, agriculture and tourism sectors of developing oil exporting countries - Abdlaziz, Rizgar Abdlkarim (2019)
This study investigates the impact of oil revenue on economic growth, agriculture and tourism in developing oil-exporting countries, which are divided into major and minor oil-exporting countries based on their oil revenue shares to their respective GDPs. While developing oil-exporting countries have gained massive oil income, they suffer from Dutch disease in different manners, such as low economic growth and lagging non-oil sectors. Heterogeneities exist among developing oil-exporting countries. Panel Autoregressive Distributed Lag (ARDL) modelling is used to achieve the objectives of the study. The first objective of this study is to examine the impact of oil revenue on economic growth for 25 developing oil-exporting countries (major and minor), conditional to the different level of the real effective exchange rate. The results show that the longrun effect of oil revenue on economic growth is significant only for the full sample, while the effect is highly positive and significant in the short run for all groups. Also, the indirect effect of the marginal effect of oil revenue on economic growth is statistically insignificant for all groups. However, the indirect effect of the oil price on economic growth is statistically significant and confirms the same direction of the marginal effects of oil revenue for all groups. In the case of the major group, the indirect effect of oil price shows the symptom of Dutch disease and proving the existence of Dutch disease. That means that in major oil-exporting countries, the oil price is harmful for economic growth when the real effective exchange rate appreciates. The second objective of the present study is to investigate the impact of oil revenue on the agriculture sector of 25 developing oil-exporting countries (major and minor), conditional to the different level of the real effective exchange rate. The regression results of the baseline model indicate that oil revenue in the long and short term has adverse and highly significant effects on the value added of agriculture in the full sample, as well as in the cases of major and minor oil-exporting countries. Despite this result, the magnitude of the impact in the major oil-exporting countries is higher than that of the minor oil-exporting countries. The results of marginal effects for the minor group show that oil revenue indirectly slows down the value added of agriculture when the real effective exchange rate appreciates. Otherwise, oil revenue benefits agriculture if the real effective exchange rate depreciates. However, in the case of major group, the marginal effect shows that oil revenue decreases the value added of agriculture, even in the presence of real effective exchange rate depreciation. The third objective of this study is to find the relationship between oil revenue and the tourism sector of oil-exporting countries based on the different level of the real effective exchange rate. The estimations show a direct positive effect of oil revenue on tourism income for the entire sample, and for the minor group. The results show an adverse but insignificant for the major group. Additionally, the findings of the marginal effect of oil revenue on tourism income support the Dutch disease phenomenon for the entire sample and the major group. That means the marginal effects of oil revenue are negative and significant at the lower-level of the real effective exchange rate (appreciation) but positive and significant at the higher-level of the real effective exchange rate (depreciation). This result is contrary to the minor group but insignificant. Overall the findings and results support the hypotheses of this study, which focuses on the differential behaviour of major and minor oil-exporting countries toward economic growth and non-oil sectors (the agriculture and tourism sectors). More specifically, the results of the direct and indirect effects of oil revenue show that major oil-exporting countries suffer from Dutch disease. The results of this study have policy implications, pointing to the need to eliminate this phenomenon. First, it is necessary for governments of oil-exporting countries to adopt a fiscal policy that limits the role of spending effects as a source of appreciation to the real effective exchange rate. Secondly, policymakers should adopt and improve policy instruments that support and promote the non-oil sectors—including proper macroeconomic policy, such as enhancing public investment in the agriculture and tourism sectors. Finally, economic diversification is required. Using oil revenue to build high-quality infrastructure may improve the non-oil sectors. Then, dynamic growth in the oil sector may lead to sustainable economic growth in the long run.